Sandstone used in the historic wayside shrines in the region of Wieliczka - Schuster, Małgorzata; Smoleńska, Anna (Geotourism/Geoturystyka, 2018)
The region of Wieliczka is especially rich in various architectural structures like wayside crosses and shrines. The great number of these objects is connected with the folk culture, religious customs of Poles as well as an easy access to a suitable stone material, which is commonly used to build those structures. Wayside shrines, as a work of folk artists, were built of dolnoistebnianski sandstone, which quarries are characteristic for the region. The condition of stone building’s wayside shrines depends on the location (near to Cracow agglomeration), and biological and mechanical factors. Over the years, they have caused a rapid process of stone destruction. Conservatory work and revaluation of most of wayshrines seem to be necessary in order to restore their original beauty.